Business cycle characteristics of Mediterranean economies: a secular trend and cycle dynamics perspective - Anna Solms; Bernd Süssmuth (International Economics and Economic Policy, 2022)
This study analyzes business cycle characteristics for all 20 major contemporaneous economies bordering the Mediterranean Sea based on annual real gross domestic product series for the period from 1960 to 2019. The region we investigate corresponds to the Mare Internum region of the Imperial Roman Empire during the Nerva-Antonine and early Severan dynasty, i.e., at the time of the maximum extent of the Roman Empire around 100 to 200 CE. The covered area encircles the Mediterranean, including economies now belonging to the European Union as well as acceding countries, Turkey, and the Middle East and North African economies. Using a components-deviation-cycle approach, we assess level trends and relative volatility of output. We also quantify the contribution of various factors to the business cycle variability within a region. We find cyclic commonalities and idiosyncrasies are related to ancient and colonial history and to contemporaneous trade relationships. Caliphate and Ottoman Empire membership as well as colonial rule in the twentieth century and contemporary Muslim share of population are the most promising predictors of business cycle commonalities in the region.
Keywords: C20; E32; N10; 330; Highpass-bandpass filtering; Historical Europe-Levant-MENA area